Development, characterization and anti-cancer activity of liposomal doxorubicin hydrochloride with palm oil / Bahareh Sabeti - Bahareh, Sabeti (2017)
Doxorubicin hydrochloride is an anticancer medicine for treatment of various kind of cancer. Anticancer drugs are known to be highly toxic agent which may kill normal cells while inhibiting the growth of cancer cells. As drug molecules may not be able to distinguish among healthy organ’s cells and cancerous cells. Similar to other anticarcinoma medicine, doxorubicin causes many side effects such as cardiotoxicity, myelosuppression, hematologic toxicity, secondary leukemia, extravasations, hepatic Impairment, alopecia and fatigue. Several studies in field of drug delivery technology have been carried out in order to minimize side effects with enhancing therapeutic effect of doxorubicin. Liposomal drug delivery system had been proven to be one of the delivery techniques for such purpose. Encapsulating doxorubicin within liposome would decrease its toxicity and do not alter its biological activity which lead to increase its antitumor potency. Liposomal doxorubicin is FDA approved anti-cancer for treatment of ovary, lung and breast cancer. This study aimed to prepare liposomal doxorubicin using palm oil (as a part of drug delivery system) which is also known to act as a natural anticancer and antioxidant. Palm oil is rich in natural ß-carotene, γ-carotene, tocopherols and tocotrienols which may support the antioxidant and anticarcinogenic activities of anticarcenoma medicine as well. Liposome formulations were designed in this study by various porpotion of palm oil and phosphatydilcholin. Six formulations containing 0, 5%, 10%, 15%, 20% and 25% of palm oil were prepared through reverse-phase evaporation method. Formation and morphology, particle size distribution, zeta potential, entrapment efficiency and in-vitro drug release and liposome degradation of each formulation were evaluated. Liposome with 10% & 15% of palm oil showed fine formation, satisfactory zeta potential, controlled releasing pattern and less degradation compare with other formulations. Further to develop the entrapment efficiency of liposomes, liposome formed by freeze-thaw method and pH gradient technique were carried out to active drug loading within vesicles. Entrapment efficiency and in vitro drug release of liposome assessed using HPLC device. The HPLC results show liposome entrapment efficiency rose up to 98% by active loading with suitable and organized release pattern. Evaluation the cellular uptake and toxicity (MTT assay) of liposomal doxorubicin hydrochloride and Caelyx® (commercial form of pegilated liposomal doxorubicin) on MCF7 and MDA-MBA 231 breast cancer cells present the higher cellular uptake and effective toxicity on cancerous cells. Distribution of liposomal doxorubicin in rat organs studied using in vivo imaging device. Images of rat organs after intracardiac injection of liposomal doxorubicin displayed less accumulation of doxorubicin in rats’ heart but more in liver, kidney and lungs. In conclusion the results of this study proved the potential application of palm oil in preparation of liposomal. Significant proportion of palm oil utilize in formulations would improve the physical properties of liposome such as shape, stability, releasing pattern and degradation. Furthermore liposome containing palm oil showed higher uptake and IC50 which develop therapeutic index and desirable bioavailability as well.